Juridical Review on Death Penalty in Indonesia (A Critical Review of the New Criminal Code) - lalu alex (Yayasan Tranformasi Aksara Digital, 2024)
The application of the death penalty remains a contentious issue throughout the world, including in Indonesia, where the death penalty continues to spark debate and controversy. With the imminent enactment of the New Criminal Code, a critical examination of the legal aspects surrounding the death penalty becomes imperative. The purpose of this study is Specifically, this study aims to interpret the meaning of the phrases “regret” and “improve oneself”, and to evaluate their significance in determining criminal responsibility and sentencing in death penalty cases. This study uses a normative legal approach, which involves the analysis and interpretation of legal principles, statutes, and court decisions relevant to the death penalty in Indonesia. This analysis reveals that the interpretation of the terms “regret” and “improve oneself” in the context of the death penalty is nuanced and diverse. Although these concepts are integral to the assessment of criminal culpability and potential for rehabilitation, their subjective nature poses challenges in the application of the law